Hydrogel coating flexible pH sensor system for fish spoilage monitoring. (December 2022) - Mu, B.; Dong, Y.; Qian, J.; Wang, M.; Yang, Y.; Nikitina, M.A.; Zhang, L.; Xiao, X.
Abstract: A hydrogel coating flexible pH sensor system is described for real-time wireless monitoring of fish spoilage. On absorption of the acidic or basic volatiles the hydrogel pH changes, which in turn changes the voltage across the pH-sensitive electrode pair shifting the response potential of the sensor. The sensitivity of the flexible pH-sensitive electrode pair in different pH standard buffers is −49.184 mv/pH. In the process of fish deterioration, ammonia is the main component of volatile gas. Therefore, we used ammonia gas as the detection object to explore the response law of the pH sensor to volatile gases. At the same time, we also investigated the effects of temperature and hydrogel coating thickness on sensor performance. Finally, we integrate the pH sensor with the flexible battery-free wireless electronic system (FBES) for wireless signal transmission. By comparing the gained sensor potential signal with the content of TVB-N in tilapia, the results demonstrate that the sensor response is closely related to the content of TVB-N in fish samples. Under storage conditions of 4 °C, 12 °C, and 20 °C, the sensor can clearly identify when the expiration of fish shelf life (15 mg/100 g) occurs. The results show the potential for monitoring fish spoilage in real-time. Graphical abstract: Image 1 Highlights: Developing a hydrogel coated flexible pH sensor system for TVB-N. Fabricating flexible pH sensor by facile process with laser direct scribing. Realizing accurate, convenient and long-term wireless monitoring for fish spoilage. Ensuring quality and safety of fish in storage and transport process.